Risk Factors and Coping Style Affect Health Outcomes in Adults With Type 2 Diabetes. (January 2016) - Huang, Chiung-Yu; Lai, Hui-Ling; Lu, Yung-Chuan; Chen, Wen-Kuei; Chi, Shu-Ching; Lu, Chu-Yun; Chen, Chun-I
Objective: Most psychosocial interventions among individuals with Type 2 diabetes mellitus (T2DM) target depressive symptoms (DSs) rather than causal antecedents that lead to DSs or affect health-related quality of life (HrQoL). This research investigated a conceptual model of the effects of risk factors and coping styles on HrQoL and DSs in patients with T2DM. Method: A descriptive, correlational design was used with a convenience sample of 241 adults with T2DM aged ≥ 20 years recruited from a hospital metabolic outpatient department. Data were collected using a demographic questionnaire, the modified Ways of Coping Checklist, the Center for Epidemiological Studies Depression Scale, the Short Form 36 Health Survey, and physiological examination. HbA1 C was collected from participants' medical records. Structural equation modeling techniques were used to analyze relationships among risk factors, mediators, and HrQoL. Results: Younger age, more education, and longer duration of diabetes predicted better physical quality of life. Duration of diabetes and three coping styles predicted DSs. Longer duration of diabetes and lower fasting glucose predicted better mental quality of life. Three coping styles acted as mediators between risk factors and health, that is, active and minimizing styles promoted positive outcomes, while avoidance promoted negative outcomes. Conclusions: This integrated model provides a holistic picture of how risk factors and coping style influence HrQoL and DSs in individuals with T2DM. Nurses could use active coping strategies in cognitive behavioral therapy to enhance glycemic control in patients with T2DM.